Desentralisasi Fiskal Dan Pertumbuhan Ekonomi Kabupaten/ Kota Di Propinsi Bali - Yusi Pramandari; David Kaluge (Trunojoyo University of Madura, 2017)
Economic growth is one of the goals of national development. The decentralization policy implemented Indonesia currently provides opportunity for each region to develop the potential of the area, so that each region is able to achieve an economic growth rate that make walfare for community analysis used in this paper is a multiple linear regression with panel data (pooling data) 9 (nine) districts in Bali Province 2009-2015. Year period of data analysis showed that Pendapan Asli Daerah and Dana Perimbangan affect the economic growth of the district in the province of Bali. Pedapatan Asli Daerah (PAD) and a real positive influence on economic growth district in Bali Province, Dana Perimbangan partially negatively affect economic growth in the district in the province of Bali during the period from 2009 - 2015 increased economic growth in an era of fiscal decentralization have not fully followed by the distribution of economic growth districs in Bali Province. This is evidenced by the Williamson index value stood at 0,687, which means there is still inequality regional GDP per capita among districts in Bali Province. Still there is an imbalance between districts shows that the achievement of development objectives are not yet capable of prospering society.